Vocational Rehabilitation Based Recovery of Patients With Mental Disorders (ODGJ) - Akasyah, Wildan; Santosa, Winanda Rizki Bagus (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This type of research is pre-experimental which will be conducted on 40 people with mental disorders without using a control group. The sampling technique used in this study was total sampling. This research was conducted by filling out questionnaires to respondents to determine coping and psychological resistance pre and post after the intervention. The analysis used was a paired t-test. There was an increase in coping scores and psychological resilience after the intervention, although there were still a few and many had fixed scores. The level of significance of the relationship with the paired t-test gave a result of = 0.026 for coping and 0.017 for resistance. The interpretation of the paired t-test was that there was a difference between before and after treatment because the p-value was <0.05. Vocational Rehabilitation is an activity that has a positive impact on the development of ODGJ (people with mental disorders).